Strengthening Community Involvement in SIMRS Implementation at Leuwiliang Hospital to Support Regional Economic Development - Asruhi, Slamet; Asropi, Asropi (Yayasan Riset dan Pengembangan Intelektual, 2025)
Community participation in supporting technological change is very much needed to run effectively and efficiently. Low community participation will hinder the technological change that is being implemented. The purpose of this study is to increase community participation in utilizing the Hospital Management Information System (SIMRS) at Leuwiliang Hospital. This study uses a qualitative approach. Data were collected through interviews, observations and secondary data, then the data were analyzed qualitatively using the Lawrence Green concept approach (predisposing factors, enabling factors, reinforcing factors) and analyzed with SWOT IFAS and EFAS. The results of the study showed that there were several factors causing low community participation in utilizing SIMRS, namely predisposing factors in the form of knowledge, attitudes, beliefs, culture and community characteristics. Enabling factors consisting of the availability of facilities, accessibility or ease of the system, supportive policies and community commitment and Reinforcing factors consisting of hospital staff, opinions from others, community support, the influence of friends and the environment. The strategy that can be used to increase community participation in utilizing SIMRS is an aggressive strategy, utilizing strengths to capture opportunities, including first increasing the optimization of the use of integrated SIMRS as the main instrument in supporting digital-based services, in line with national policies that require the use of information technology in health services, second encouraging the strengthening of the image of the hospital as a type B referral hospital with superior specialist services to expand the reach of the service area to cover all potential sub-districts, third developing sustainable and promotive and preventive health services based on SIMRS data in responding to the trend of increasing life expectancy and the need for long-term services.